Peran Orang Tua dalam Mendampingi Anak Berkebutuhan Khusus dengan ADHD dan Speech Delay di Rumah di Masyarakat Desa Kartika Bhakti - Nisa Nikmatul Azizatus Sidiqoh; Aulia Ratnasari; Mirna Wati; Nabila Az-Zahra; Andela Oktavia; Surawan Surawan (Politeknik Kesehatan Kemenkes Surakarta, 2026)
Background: Children with Attention Deficit Hyperactivity Disorder (ADHD) and speech delay require special support to foster the development of their attention and communication skills. In settings where access to therapy is limited, the role of parents becomes particularly important. Objective: This study aims to describe the role of parents in supporting children with ADHD and speech delay at home. Methods: This study employed a qualitative approach using a descriptive method. Data were collected through interviews and documentation. The study subjects were parents of a seven-year-old child diagnosed with ADHD and speech delay. Results: Parents act as caregivers, educators, and providers of stimulation through activities the child enjoys, the use of books and videos, and word repetition. Challenges faced include speech difficulties, hyperactive behavior, and limited access to therapy. Conclusion: Parents’ active role, patience, and consistency in providing stimulation at home positively contribute to the development of children with ADHD and speech delay. Keywords: The Role of Parents, ADHD, Speech Delay.